THE EFFECT OF HEDONIC LIFESTYLE, HEDONIC MOTIVATION AND QUALITY OF PRODUCTS TO INTEREST RECYCLING TUPPERWARE PRODUCT IN JAMBI CTY - Johannes Johannes; Ade Octavia; Yemmi Suwarti (Journal of Business Studies and Management Review, 2017)
This study aims to analyze the influence of hedonic lifestyle, hedonic motivation and product quality simultaneously and partially to the interest of buy back Tupperware product in Jambi City. The population is Tupperware consumers in PT. Nazila Jambi Nugraha which amounted to 28,106 members. After doing research data that can author though only 139 questionnaires. Data collection method in this study using survey method, followed by statistical methods to test the hypothesis is by multiple linear regressions (multiple regressions). The results showed that the hedonic lifestyle, hedonic motivation and product quality had a positive and significant influence on repurchase interest. Where product quality has a more dominant influence when compared to two other variables. Based on the results of the study for it is expected to the future management company can continue to maintain and improve product quality one of them is by diversifying the product. Keywords: Hedonistic lifestyle, hedonic motivation, quality of products and repurchase intention.